Enhancer-promoter communication at the Drosophila engrailed locus. - Kwon, D.; Mucci, D.; Langlais, K.K.; Americo, J.L.; Devido, S.K.; Cheng, Y.; Kassis, J.A. (Development, 2009)
Enhancers are often located many tens of kilobases away from the promoter they regulate, sometimes residing closer to the promoter of a neighboring gene. How do they know which gene to activate? We have used homing P[en] constructs to study the enhancer-promoter communication at the engrailed locus. Here we show that engrailed enhancers can act over large distances, even skipping over other transcription units, choosing the engrailed promoter over those of neighboring genes. This specificity is achieved in at least three ways. First, early acting engrailed stripe enhancers exhibit promoter specificity. Second, a proximal promoter-tethering element is required for the action of the imaginal disc enhancer(s). Our data suggest that there are two partially redundant promoter-tethering elements. Third, the long-distance action of engrailed enhancers requires a combination of the engrailed promoter and sequences within or closely linked to the promoter proximal Polycomb-group response elements. These data show that multiple mechanisms ensure proper enhancer-promoter communication at the Drosophila engrailed locus.